Role of αENaC in root resorption of adjacent teeth due to entirely impacted mandibular third molars - Jiaqi Tang; Weijun Yu; Lu Lin; Ruhan Yang; Guanglong Li; Min Jin; Yuting Gu; Bin Jiang; Eryi Lu (BMC Oral Health, 2024)
Abstract Background Entirely impacted mandibular third molar (EIM3M) concerns the pathological external root resorption (ERR) of the adjacent mandibular second molar (M2M) and formation of granulation tissue between two molars. The study aimed to clarify the effect of αENaC, a mechano-sensitive molecule, to explore the mechanical mechanism in this scenario. Methods The force EIM3M exerted on M2M was proved by finite element analysis. αENaC expressions were tested by real-time polymerase chain reaction (PCR), immunoblotting and immunofluorescence. Inflammatory and epithelial-mesenchymal transition (EMT)-related molecules expressions were also detected by real-time PCR. The correlation was analyzed by Spearman’s correlation analysis, and receiver-operator characteristic (ROC) curve was further exhibited. Results The force was concentrated in the ERR area. αENaC was upregulated, positively correlated with ERR degree and localized to the fibroblasts in ERR granulation tissues. Moreover, αENaC was respectively and positively associated with elevated TNF-α and N-cadherin in ERR granulation tissues. More importantly, ROC analysis verified αENaC as a novel indication of the incidence of this disease. Conclusions Our finding revealed the force from EIM3M causing ERR of M2M, and elucidated the expression and localization of αENaC and its positive correlation with inflammation, EMT and disease severity, suggesting a novel indication in this disease.